Acute Minocycline Treatment Mitigates the Symptoms of Mild Blast-Induced Traumatic Brain Injury - Kovesdi, Erzsebet; Kamnaksh, Alaa; Wingo, Daniel; Ahmed, Farid; Grunberg, Neil E.; Long, Joseph B.; Kasper, Christine E.; Agoston, Denes V. (Frontiers in Neurology, 2012)
Mild blast induced traumatic brain injury (mbTBI) and its associated memory impairment and anxiety elevation currently represent one of the major military health challenges. Our earlier work using a rodent model of mbTBI indicated that the pathology underlying the observed neurobehavioral abnormalities includes neuroinflammation. The aim of our present study was to determine the effect of acute treatment with minocycline, an FDA approved non-steroidal anti-inflammatory drug, on the functional and molecular outcomes of mbTBI. Beginning four hours after a single exposure to mild blast overpressure, animals received a daily dose of minocycline (50 mg/kg) or physiological saline intraperitoneally (i.p.) for 4 days. Physiological parameters (arterial blood O2 saturation, heart and breath rates, and pulse distension) and neurobehavior (locomotor activity, anxiety, and spatial memory) were monitored at multiple time points. At the termination of the experiment (51 days post-injury), we analyzed sera and select brain regions for changes in protein markers of inflammation as well as vascular, neuronal, and glial integrity. We found that acute treatment with minocycline completely prevented memory impairment and anxiety development by ameliorating the inflammatory response to injury and substantially reducing neuronal and glial cell loss. Based on our findings, we urge testing the effect of minocycline treatment in human mbTBI.